Analysis Of Completeness Of Nursing Care Documentation Through Supervision Activities - Helsy Desvitasari (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2022)
ABSTRACT Completeness of nursing care documentation is an important part of service within the scope of the hospital. Efforts that can be made in improving the quality of service, one of which is through supervision activities. Supervision can be carried out by the head of the room to the implementing nurse in the fulfillment of nursing care, including the documentation process. The purpose of this research is to increase the completeness of documentation of nursing care through supervision activities. This research uses a pre-experimental design (One Group Pre-post Test Design). Purposive sampling technique with the number of nurses 30 people. Data analysis using Paired T test with p value = 0.001. The results showed that the average completeness of nursing care documentation before supervision was 75.5%. The average completeness of nursing care documentation after supervision was 89.6%. There is a significant effect of the implementation of supervision on the completeness of nursing care documentation with a mean value of – 13,000 and p = 0.001. The conclusion of this study shows that there is an effect of the completeness of nursing care documentation before and after supervision. It is recommended that the head of the room can be more intense to evaluate the existing documentation both in writing and through online (electronic media). Keywords: Supervision and Documentation of Nursing Care